Peningkatan Kompetensi Guru SMA di Cilegon Banten melalui Media Pembelajaran Daring - Reni Oktaviani; Nur Sekhudin; Selly Oktarini (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service aims to improve teacher competence through online learning media. This learning media will help teachers in carrying out online learning during the pandemic. The method applied in this activity is the demonstration method. This method is a method that is carried out by demonstrating and explaining the procedures for doing something through demonstrated examples or experiments. The online learning media practiced in this activity are Google Classroom, Zoom Cloud Meetings, Kahoot, and Quizizz. The result of this activity is that teachers can create and utilize online learning media to facilitate the learning process.